Literatura, borracha, banana: Brasil e Honduras no século XX - Valdez, Darwin Ariel Amador (2021)
Through hermeneutics and comparative studies, we relate the literature, economics, history and sociology of Rubber, in the Brazilian Amazon, and of Bananeiras, in Honduras, phenomena that occurred in the 20th century. For this study, we will focus on the w orks of Ramón Amaya Amador (19161966), from Honduras, with emphasis on the novel “Prisión Verde” and Álvaro Maia (18931969), from Brazil, with the novel “Beiradão”. At first, the social, political and economic characteristics of Rubber and Banana are con trasted, emphasizing in the beginning of the two, the consequences after their falls and the system of socioeconomic relations of the aviation that happened in these two phenomena. Thus, in a second moment, we compare the implications of these phenomena on the aesthetics and literature of Brazil and Honduras at that time. We return to the Latin project of aesthetic independence, developed by the theorist Ángel Rama, and, based on that, with the help of Georg Lukács' theory, we discussed the relationship bet ween literary experience and class consciousness. Finally, through comparative literature, we analyze the effects of Rubber and Banana on human events, based on the literature and its relationship with other areas. This reflection arises on a theoretical b asis in authors such as HansGeorg Gadamer, from Hermeneutics; Steven Tötösy de Zepetnek, Armando Gnisci and Gilbert Chaitin from Comparative Literature.